The response of Bacillus licheniformis to heat and ethanol stress and the role of the SigB regulon. Issue 14 (18th July 2013) - Voigt, Birgit; Schroeter, Rebecca; Jürgen, Britta; Albrecht, Dirk; Evers, Stefan; Bongaerts, Johannes; Maurer, Karl‐Heinz; Schweder, Thomas; Hecker, Michael
<x xml:space="preserve">Abstract</x> The heat and ethanol stress response of Bacillus licheniformis DSM13 was analyzed at the transcriptional and/or translational level. During heat shock, regulons known to be heat‐induced in Bacillus subtilis 168 are upregulated in B. licheniformis, such as the HrcA, SigB, CtsR, and CssRS regulon. Upregulation of the SigY regulon and of genes controlled by other extracytoplasmic function (ECF) sigma factors indicates a cell‐wall stress triggered by the heat shock. Furthermore, tryptophan synthesis enzymes were upregulated in heat stressed cells as well as regulons involved in usage of alternative carbon and nitrogen sources. Ethanol stress led to an induction of the SigB, HrcA, and CtsR regulons. As indicated by the upregulation of a SigM‐dependent protein, ethanol also triggered a cell wall stress. To characterize the SigB regulon of B. licheniformis, we analyzed the heat stress response of a sigB mutant. It is shown that the B. licheniformis SigB regulon comprises additional genes, some of which do not exist in B. subtilis, such as BLi03885, encoding a hypothetical protein, the Na/solute symporter gene BLi02212, the arginase homolog‐encoding gene BLi00198 and mcrA, encoding a protein with endonuclease activity.